Synthesis of Some New Chalcones, 3-Aroylflavanones, 3-Aroylchromanones and their Derivatives as 1-Aryl-3-(2-Hydroxy-5-methyphenyl)-5,5-diakyl/5,5-Diaryl/5-Aryl/4-Aryl-Δ2-Pyrazoline - Dighade, S.R.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
(i) Seven different chalcones I(a)-I(g) were synthesised by condensing 2-hydroxy-5-methylacetophenone with two ketones and five aromatic aldehydes in ethanol in presence of alkali. (ii) I(a)I( g) were reacted with phenylhydrazinehydrochloride in pyridine medium to give II(a)-II(g)-Δ2-pyrazolines. (iii) III(a)-III(g) 3- aroylflavanones and 3-aroylchromanones were synthesised from 1,3-propandedione by literature method. (iv) III(a)-III(g) were reacted with phenylhydrazinehydrochloride in pyridine medium to give IV(a)-lV(g) 1-aryl-3,5-diaryl-4-aroyl- Δ2 -pyrazolines. The structures were confirmed on the basis of chemical and spectral analysis.